Women empowerment and leadership in Islam: between myth and reality - Osmani, Noor Mohammad; Farooq, Mohammad Omar; Ahmad, Abu Umar Faruq (World Scientific, 2020)
Orthodox Muslim scholars are in general agreement that women are not entitled to hold the leadership or the topmost public office of a nation. Many scholars hold even a more restrictive view on the issue as to whether it is due to Qur’anic texts and Prophetic traditions (ahadith) that women are barred from key positions, or it is largely due to socio-cultural and economic settings of a society. The Qur’an urges the Prophet’s wives (nisa an-nabiyy) to stay quietly at their homes and not to make dazzling displays like that of the time of primitive ignorance (33:33). It is also commonly cited from the Qur’an that men are the caretakers/guardians in charge (qawwamun) of women (4:34). The only Prophetic tradition regarding women’s leadership is that the Prophet (S) is reported to have said, “Never will succeed such a nation as lets their affairs carried out by a woman” (Sahih al-Bukhari, 4425; Sunan of An-Nasai, 8/227). On the other hand, the Qur’an also affirms that the believers, both men and women, are guardians (awliya’) of one another (9:71). Also, since the Qur’an acclaims the Queen of Sheba for her just rule, such prominent scholars as Imam Abu Hanifa, Imam al-Tabari and Ibn Hazm support that women could hold the topmost judicial position. Ibn Hazm also asserts that there is no theoretical prohibition for women to carry out the mission of Prophethood. Naturally, if they could be Prophets, they could also be the leaders, for the Prophets are the leaders. This chapter aims to explore these issues and examine by primarily analyzing the Qur’anic verses, Prophetic traditions, the heritage of the Rightly- Guided Caliphs and the rulings of Muslim jurists. In modern times, the quest for women empowerment is integrally related to the issue of leadership. This chapter will critically evaluate the validity of the quoted hadith, and examine its contexts in order to understand how and why the Prophet (S) would have stated as such. This analysis is crucial to address present-day realities, as a significant number of Muslim women have competently led their nations by holding topmost offices. Finally, this presentation hopes to shed light on what the real political status of Muslim women should be today in light of the Qur’an, Sunnah and juristic discourse. Resolution of the issue of leadership can significantly impact the women empowerment from Islamic perspectives.